76 Evaluating Nitrogen Management Strategies to Improve Southern Bermudagrass Grazing Systems. (28th November 2020) - Burt, Justin C; Tucker, Jennifer J; Baxter, Lisa
Abstract: Bermudagrass (Cynodon dactylon) is one of the most common perennial warm-season forage crops grown in the South. While prominent in the region bermudagrass management requires large amounts of fertility and forage quality is moderate at best. Incorporating a legume into bermudagrass pastures could serve as an alternative to the necessary applications of synthetic N, while also improving the nutritive value of the forage base. A two-year grazing evaluation was conducted from May-Sept. 2018 (Y1) and May-Aug. 2019 (Y2) at the University of Georgia Tifton Campus in Tifton, Georgia, to compare concurring production of alfalfa/bermudagrass mixed pastures (BGA) with bermudagrass monoculture pastures with (BGN) or without (BGZ) the application of synthetic nitrogen. The experimental design was a randomized complete block with three treatments and two replications. All paddocks were evaluated pre and post grazing event for herbage availability, botanical composition, forage species competitiveness, and nutritive value. Paddocks (0.8-ha) were rotationally grazed using put and take management with stocker steers (Y1 BW=195.9±22.9 kg; Y2 BW=228.5±30.0 kg), two testers per treatment. Steers were weighed at initiation, conclusion, and on a 28–30 day interval for calculation of ADG and gain/ha. Statistical analysis was conducted using the PROC MIXED procedure of SAS. Despite significant drought in Y2, year did not affect total gain/ha, however treatment did (P = 0.04), such that BGA was highest (383.6±35.1 kg/ha), and BGN and BGZ were not different (261.2±35.1 kg/ha and 239.0±35.1 kg/ha, respectively). This is likely due to the lower stocking density and inclusion of high-quality volunteer annual grasses in BGZ treatments which allowed for selective grazing. These data suggest that rotationally grazing alfalfa/bermudagrass mixtures can result in a higher gain/ha, than bermudagrass pastures that are supplemented with or without synthetic N in the South.